Edukasi Vaksinasi Covid-19 bagi Ibu Hamil dan Menyusui di Desa Percut SeiTuan Deli Serdang - Yunida Turisna Octavia; Julia Mahdalena Siahaan; Frida Liharris Saragih (Yayasan Inspirasi El Burhani, 2022)
Background: Acceptance of the Covid-19 vaccine for pregnant and lactating women is still very low, one of the things that causes it is the lack of education regarding the benefits of the Covid-19 vaccine itself, this causes the reluctance of pregnant and lactating women to vaccinate against Covid-19. Pregnant women infected with Covid-19 are at risk for abortion and premature birth and breastfeeding mothers are also one of the vulnerable groups exposed to Covid-19. Meanwhile, pregnant women have a very vulnerable immune system so special attention is needed to avoid being exposed to Covid-19, so also with mothers who are breastfeeding if they do not get the Covid-19 vaccination, it is feared that they will be exposed to Covid-19 and transmit it to their babies. Objective: The purpose of this activity is to provide counseling related to Covid-19 vaccination education for pregnant and lactating mothers. Method: The method of implementing this activity is counseling related to Covid-19 vaccine education for pregnant and lactating women, the partner in this service activity is Percut Sei Tuan Village. Result: After delivering counseling to 31 pregnant and breastfeed mothers who gave positive and useful effect, pregnant and breastfeed mothers in Percut Sei Tuan village understood the importance of the Covid-19 vaccination and the risk if mothers were exhibited to this virus. Conclusion: The conclusion from the service activities was that the knowledge of pregnant women and breastfeeding mothers was getting better regarding the Covid-19 vaccination so that pregnant women and breastfeeding mothers wanted to participate in the Covid-19 vaccination. Suggestions for health workers to further increase Covid-19 vaccine education activities so that mothers' interest in getting vaccines increases.